2017
DOI: 10.18632/oncotarget.14995
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms ofESR1, UGT1A1, HCN1, MAP3K1andCYP2B6are associated with the prognosis of hormone receptor-positive early breast cancer

Abstract: In this study, we investigated whether single nucleotide polymorphisms (SNPs) identified by genome-wide association study (GWAS) (MAP3K1, FGFR2, TNRC9, HCN1, and 5p12), and SNPs involved in the metabolism of estrogen (CYP19, COMT, ESR1, and UGT1A1), tamoxifen (CYP2C9, CYP2C19, CYP3A5, and CYP2D6), and chemotherapeutic agents (ABCB1, ALDH3A1, and CYP2B6) are associated with the prognoses of 414 hormone receptor (HR)-positive early breast cancers with negative or 1 to 3 nodal metastases. At a median follow-up pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 58 publications
2
38
0
Order By: Relevance
“…Genome-wide association studies (GWAS) have identi ed several single nucleotide polymorphisms (SNPs), such as MAP3K1 (Mitogen-Activated Protein Kinase Kinase Kinase 1) rs889312, associated with breast cancer risk [14][15][16]. We recently reported that MAP3K1 rs889312 is closely associated with poor disease-free survival (DFS) and overall survival (OS) in early-stage HR-positive breast cancer [17].…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have identi ed several single nucleotide polymorphisms (SNPs), such as MAP3K1 (Mitogen-Activated Protein Kinase Kinase Kinase 1) rs889312, associated with breast cancer risk [14][15][16]. We recently reported that MAP3K1 rs889312 is closely associated with poor disease-free survival (DFS) and overall survival (OS) in early-stage HR-positive breast cancer [17].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, seven SNPs (rs2046210 in ESR1, rs1219648 in FGFR2, rs3817198 in LSP1, rs3803662 in TNRC9, rs889312 in MAP3K1, rs10941679 in MRPS30 and rs13281615 in PVT-1) have been found to be strongly associated with breast cancer risk in different populations, not only Asian populations (namely Chinese, Japanese, Pakistani and North Indian), but also European (German), African (Tunisian) and Australian populations, with the majority of the P values being much lower than 0.01. Furthermore, the mutated alleles of these SNPs could increase breast cancer risk significantly with odds ratios (ORs) (and 95% confidence interval (CI)) ranging from 1.07 (1.01 -1.14) to 3.06 (1.79 -5.25) (Liang et al, 2008;Antoniou et al, 2009;Cai et al, 2011;Shan et al, 2012;Guan et al, 2014;Lin et al, 2014;Sawyer et al, 2014;Siddiqui et al, 2014;Zhang et al, 2014;Campa et al, 2015;Ghoussaini et al, 2016;He et al, 2016;Mazhar et al, 2016;Hein et al, 2017;Kuo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies on correlations between SNPs and prognosis of breast cancer, but conclusions are different. Some researchers believed that rs88931 (MAP3K1) was highly correlated with distant disease‐free survival (DDFS), DFS, and OS of hormone receptor‐positive breast cancer (Kuo et al, ). Yamamoto‐Ibusuki et al () confirmed that homozygous alleles of rs2046210 showed worse relapse‐free survival.…”
Section: Discussionmentioning
confidence: 99%